Pengaruh Model Discovery Learning Berbantuan Audio Visual Terhadap Hasil Belajar Peserta Didik Kelas VII Pada Di SMPN 1 Nagawutung Lembata - Maria Agustina Masi Tukan; Florentina Yasinta Sepe; Sardina Ndukang (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2024)
The students' learning outcomes are still low due to the teaching model used by teachers being suboptimal and the lack of utilization of learning media. A teaching model that can address this issue is the Discovery Learning model. The purpose of this study is to determine the effect of the Discovery Learning model assisted by audiovisual media on the learning outcomes of Grade VII students on the topic of Interactions Between Living Organisms and Their Environment at SMPN 1 Nagawutung Lembata during the 2023/2024 academic year. This research employs a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The sampling technique used is purposive sampling. Data analysis techniques include descriptive data analysis and inferential data analysis. The study results show that the average learning outcomes of students in the experimental class applying the Discovery Learning model assisted by audiovisual media were as follows: pretest average score of 50.15, posttest average score of 81.56, and N-Gain of 0.62, categorized as high. Meanwhile, the control class using the direct teaching model had a pretest average score of 45.15, posttest average score of 66.40, and N-Gain of 0.39, categorized as low. Based on the ANCOVA test results, the significance level was 0.043 < 0.05, indicating that the null hypothesis (H?) is rejected, and the alternative hypothesis (H?) is accepted. Based on these findings, it can be concluded that the Discovery Learning model assisted by audiovisual media affects the learning outcomes of Grade VII students on the topic of Interactions Between Living Organisms and Their Environment at SMPN 1 Nagawutung Lembata during the 2023/2024 academic year.